OIC movement for stronger political community - Ahmed, Yaakob; Ismail, Ahmad Faris; Ra'ees, Wahabuddin (2017)
The Organization of Islamic Cooperation (OIC) has come of age and been established to revive the Muslim World and improve the relations among the Muslim states. It seems that everyone hopes that OIC will unite the Muslim World into one whole organic community and thus reviving the Glorious day of Islamic Civilization. However, the Charter of the Organization bear testimony to the fact that the founding fathers of the Organization were humble and were cognizant of the political reality of the Muslim that they did not contemplate Uniting the Muslim world into an organic whole. However, Muslim states should work closely to achieve the objectives of the Organizations Charter.